Telaah Kitab Tafsir Firdaus Al-Na’im Karya Thaifur Ali Wafa Al-Maduri - Moh Azwar Hairul (Nun : Jurnal Studi Alquran dan Tafsir di Nusantara, 2017)
This article aimed to describe one of the Tafsir which compiled by Ulama Madura named Thaifur Ali Wafa. He is the son of famous Ulama Madura named KH. Ali Wafa. Thaifur’s capacity as the Ulama could not be doubted. Inherited the expertise of his father, now he has produced a number of books. One of His magnum opus is Tafsir Firdaus al-Na’im. The Tafsir classified as the unpublished tafsir, so that his Tafsir considerend unnoticed on the studies of The Alquran in Indonesia. Tafsir Firdaus al-Na’im consist complete commentary of Alquran within 30 Chapter and written by Arabic language. It took approximately three year to complete his written. The Methodology of the Tafsir is using the Tahlili method. althought that, the way its explanation not totally as the same Tahlili ways. It viewed with the aspect of interpretation using ijmali analysis with simple explanation, it’s feature interpretation could not be affilated to any special pattern. The existance of the Tafsir Firdaus al-Nai’m in the modern era showed the dynamics development of interpretation of the Alquran in Indonesia. at least, this Tafsir could add the treasury of literature interpretation of the Alquran in Nusantara.